KESULTANAN SAMUDERA PASAI SEBAGAI PUSAT AWAL ISLAMISASI DI NUSANTARA : ANTARA PERDAGANGAN DAN KEKUASAAN POLITIK - Dewi Larasati, Dinda; Secilia Simamora, Agnes; Sophia Sihotang, Bella; Eriva Tampubolon, Ririn; Maulana Saleh Harefa, Fikri; Tanjung, Flores (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Sultanate of Samudra Pasai, founded on the northern coast of Aceh around the 13th century, played an important role in the Islamization of the archipelago through a system of international trade and political integration. This article discusses how Pasai became a center for the spread of Islam from Arabia, Gujarat, and Persia to the archipelago due to its function as a major port in the Strait of Malacca. Muslim traders traded spices, silk, and luxury goods. They not only brought goods, but also taught Islam to the local community. Politically, the Sultanate of Pasai built its hegemony through dynastic alliances, elite marriages, and military expansion, strengthening Islam as an ideology of power. Archaeological evidence such as the tomb of Sultan Malikussaleh (1297 AD) and the Hikayat Raja-Raja Pasai manuscript show a blend of local Malay traditions and Islamic law. This process resulted in a peaceful but successful model of Islamization, which had an impact on kingdoms such as Malacca and Demak. Combining primary sources (classical Islamic texts and inscriptions) with an analysis of Marco Polo and Ibn Battuta's trade networks, this article uses an interdisciplinary approach. The main findings show that economic-political cooperation accelerated mass conversion and shaped the Islamic identity of the archipelago, which was the key to Pasai's success. This study enhances our understanding of the dynamics of religious globalization in Southeast Asia before colonialism.